Changes in the fatty acid profile of fish oil derived from Pangasius catfish (Pangasianodon hypophthalmus) processing waste due to variations in fish size and heating temperatures [version 2; peer review: 2 approved] - Andarini Diharmi; Edison Edison; Netti Aryani; Benny Heltonika; Indra Suharman (F1000Research)
Background During the last decade, the demand for fish oil as a feed component has increased. Therefore, identifying sources of fish oil from processed catfish waste is an important task. This study aimed to analyse the relationship between fresh weight and mesenteric weight in each group of fish and determine how variations in the size of catfish (Pangasianodon hypophtalmus) and heating temperature affect fatty acid profiles. Methods The primary source of raw material used to produce fish oil is the mesenteric organ, specifically the belly fat of catfish. This material was obtained from catfish in the following categories: Group A (290-390 g), Group B (440-685 g), and Group C (890-1,100 g). The fish oil was subjected to four different levels of heating temperature (45°C, 60°C, 75°C, and 90°C). The parameters that were analysed included biometry measurements, the correlation between fish weight and mesenteric tissue, and fatty acid content. Results Significant positive linear correlations were found between body weight and mesenteric tissue in Group A (p < 0.001, r 2 = 0.65), Group B (p < 0.001, r 2 = 0.72), and Group C (p < 0.001, r 2 = 0.64). Notably, significant differences in fatty acid composition were observed among fish groups and varied heating temperatures. Within the fish group, unsaturated fatty acids ranged from 51.25% to 56.61%, n-3 fatty acids from 1.44% to 1.77%, n-6 fatty acids from 9.04% to 10.1%, and n-9 fatty acids from 35.35% to 37.43%. Temperature fluctuations led to unsaturated fatty acid contents of 52.06% to 55.55%, n-3 fatty acids of 1.28% to 1.46%, n-6 fatty acids of 8.14% to 8,45%, and n-9 fatty acids of 34.9% to 36.92%. Conclusions The best fatty acid composition in fish oil was found in Group B (with a weight between 440 g to 685 g) through a heating process at 45°C